Bank Risk-Taking and Bank Rents: Revisiting the Franchise Value Hypothesis - Gianni De Nicolò (CESifo GmbH, 2025)
Using a large sample of US Bank Holding Companies during 1995-2023, we find that a standard measure of franchise value predicts lower bank capitalization and higher bank risk of insolvency. The franchise value hypothesis (FVH), postulating a negative relationship between bank franchise value and bank risk-taking, is thus rejected in our sample. We then construct proxy measures of bank pricing power rents and rents due to government guarantees, and show that an increase in either type of rents is associated with higher franchise values. Furthermore, higher rents are positively and significantly associated with higher operating costs, suggesting the existence of a rent-efficiency trade-off. To rationalize our empirical findings, we calibrate two standard financial models of the banking firm and examine the theoretical implications of a banking industry model featuring imperfect competition, agency costs, and endogenous market structure. These models support FVH incentive mechanism, but equilibrium outcomes do not necessarily imply a negative relationship between franchise value and bank risk-taking.
Keywords: C21; E44; G21; 330; Tobin Q; bank risk of insolvency; bank rents